2006
DOI: 10.1002/jmri.20638
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cardiac volumes and mass with FLASH and SSFP cine sequences at 1.5 vs. 3 Tesla: A validation study

Abstract: Purpose:To compare cardiac cine MR imaging using steady state free precession (SSFP) and fast low angle shot (FLASH) techniques at 1.5 and 3 T, and to establish their variabilities and reproducibilities for cardiac volume and mass determination in volunteers. To assess the feasibility of SSFP imaging in patients at 3 T and to determine comparability to volume data acquired at 1.5 T. Materials and Methods:Ten healthy volunteers underwent cardiac magnetic resonance imaging using SSFP and segmented gradient-echo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 25 publications
5
63
1
1
Order By: Relevance
“…Wintersperger et al (9) compared LV volumetric measurements between 1.5T and accelerated 3T studies using TSENSE, but neither myocardial mass nor RV volumetric data were presented, and only ten subjects were studied. Hudsmith et al (27) reported interstudy variability of cardiac measurements at 1.5T and 3T, but only four healthy volunteers were evaluated and parallel imaging was not used. Finally, Grothues et al reported interstudy variability of LV (4) and RV (3) measurements by serial 1.5T CMR, but the studies utilized a gradient echo (FLASH) sequence instead of SSFP, and the impact of 3T was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Wintersperger et al (9) compared LV volumetric measurements between 1.5T and accelerated 3T studies using TSENSE, but neither myocardial mass nor RV volumetric data were presented, and only ten subjects were studied. Hudsmith et al (27) reported interstudy variability of cardiac measurements at 1.5T and 3T, but only four healthy volunteers were evaluated and parallel imaging was not used. Finally, Grothues et al reported interstudy variability of LV (4) and RV (3) measurements by serial 1.5T CMR, but the studies utilized a gradient echo (FLASH) sequence instead of SSFP, and the impact of 3T was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Left and right ventricular endocardium and epicardium of the short axis cine images were manually contoured. With the use of Argus processing (Siemens Medical Solutions, Erlangen, Germany), left and right ventricular volumes, ejections fractions, left ventricular mass, diastolic peak filling rates, and filling times were estimated (22). On average, 19 phases over each cardiac cycle were obtained.…”
Section: Measurement Of Blood Pressures Cardiac Volumes Mass and Fmentioning
confidence: 99%
“…Pilot images were acquired, followed by horizontal and vertical long axis cine images with the subjects in a supine position. A stack of steady state free precession (SSFP), short axis cine images were subsequently obtained by using breath hold and cardiac gating (22). The short axis images were obtained in a prospective manner, from the base to the apex, in 1-cm thick slices.…”
Section: Measurement Of Blood Pressures Cardiac Volumes Mass and Fmentioning
confidence: 99%
“…With the subjects in a supine position, pilot images were acquired, followed by horizontal and vertical longaxis cine images. A stack of steady-state, free precession (SSFP), short-axis cine images were subsequently obtained using breath holding and cardiac gating (Hudsmith et al, 2006). The short-axis images were obtained in a prospective manner from the base to the apex, in 1 cm-thick slices.…”
Section: Body Weight and Compositionmentioning
confidence: 99%